Accuracy and Detection Efficiency in Stacked PVC-based Transparent Markers for Augmented Reality Systems - Kurnia Prima Putra; Andi Baso Kaswar; Muh. Ihsan Zulfikar; Tri Afirianto (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
Augmented Reality (AR) marker-based tracking has evolved from single-marker systems, which limit spatial coverage and robustness, to multi-marker approaches that enable simultaneous detection for expanded interactivity. Prior research using libraries like Vuforia and AR.js has applied multi-markers in education (e.g., solar system simulations) and interactive media, improving redundancy and workspace; however, stacked transparent overlays—treating layers as unified yet distinct entities—remain underexplored, especially for alignment precision and opacity effects in translucent materials like PVC.This study evaluates tracking accuracy and detection efficiency of stacked transparent markers (2–7 layers) in AR.js, printed on 0.3 mm PVC sheets and tested with a Vivo V30 Pro camera under controlled lighting. Well-aligned configurations maintain accuracy near single-marker baselines (0.85 mm to 1.15 mm deviation), with detection rates from 98.5% to 88.3%, though processing time rises from 16.9 ms to 25.9 ms, lowering frame rates from 59.2 FPS to 38.6 FPS. Translational (2–5 mm) and rotational (5°–15°) misalignments sharply degrade performance, reducing 7-layer detection to 65.4% and 58.2%, respectively.The primary contribution is quantitative benchmarks for PVC-based overlays in AR.js, confirming feasibility for multi-layered tracking while defining tolerances (<2 mm translation, <3° rotation) to sustain >90% detection in 3–5 layers. These insights guide AR design for robust, extended applications in education and industry.